Assessing the tourism potential of Plalangan Village for sustainable agro-edutourism development - Muhammad Dzulkifli; Iqbal Erdiansyah; Milawaty Milawaty; Evio Tanti Nanita; Lely Dian Utami (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — The objective of this research is to assess the tourism potential of Plalangan Village for developing it as a tourism destination, specifically focusing on sustainable agro-edutourism.Method — This study utilized a qualitative approach with qualitative descriptive methods. Data collection involved the use of observation, focus group discussions (FGDs), and in-depth interviews with key figures. Additionally, literature studies conducted online and literature reviews were undertaken. Visual evidence in the form of documentation was employed to enhance the credibility of the research findings.Result — The research results indicate that Plalangan Village possesses tourism potential, with various attractions such as natural sites like Plalangan Hill and the Twin Dams, cultural sites like Can Macanan Kadduk, and man-made attractions like fish farming and the cracker industry. Additionally, the village has potential areas for a people's market and open green spaces. In light of this potential, a tourism map of Plalangan Village has been created, showcasing the various attractions, as well as the suggested flow of tourist visits, one-day tour packages, and a visualization of the appealing camping grounds on Plalangan Hill. These findings strongly suggest that Plalangan Village has the potential to be developed as a tourism village, with a sustainable agro-edutourism concept.Novelty — This study focused on specific regional agro-edutourism potentials and their development strategies, aiming to enhance local welfare and community prosperity through tailored approaches.